A new evaluation method of local muscular load at workplaces in Czech companies - Dombeková, Barbora; Tucek, David (Serbian Journal of Management, 2018)
In this article, the role and position of Ergonomics, Local Muscular Load Measuring, wас defined. There are two main parts of ergonomics: overall physical load and local muscle load. The measurement methods based on using muscle forces are used in the Czech Republic mainly. Other countries measure local muscular load more subjectively, through evaluation sheets (ergonomic checklists). However, in this article, the presented methods are more precise and objective. Otherwise, the employee risks exposure to occupational diseases, serious illnesses, etc. In this case, the employer is then exposed to liabilities stemming from not creating suitable working conditions, such as compensation, increased recruitment costs, etc. In the Czech Republic, management is increasingly being held liable for occupational diseases stemming from “local muscular load” of employees. In the world, it is also known as the repetitive strain injury (RSI). As a result, it is necessary to evaluate the local muscular load in Czech businesses and identify the main causes of overload. In this article, the authors will introduce a new methodology for local muscular load measuring with the datalogger equipment. The research also showed that the health and safety limits for local muscular load were exceeded in 52% of the workplaces researched. Various causes and weaknesses were identified. These could increase those risks.
Keywords: ergonomics; Occupations; loads; industry; Employees; Czechs